STRENGTH OF CEMENTS OBTAINED WITH THE ADDITIVE OF PROCESSED MINERALS - Olimov Tolmas Farkhodovich (Research Parks Publishing LLC, 2023)
the article presents the results of studies of new mineral additives on the strength properties of cements. The proposed mineral additives made it possible to obtain cements without lowering the grade. Modification of additives implies an increase and increase in the starting raw material and its chemical activity. Modified Additives have a positive effect on the properties and strength of cement. Thus, the use of fractional waste from steelmaking (FOSPP) has been established, and heat treatment of kaolin enrichment waste (TOW) as a modification of additives (AM) leads to energy savings for grinding cement and a reduction in the cost of the product. The proposed additive and methods for preparing cement additives open up a wide opportunity for recycling industrial waste in the production of cement, improves the environment in industrial region, and also stabilizes the physical and mechanical properties of cement products.